Pengembangan Media Pembelajaran Video Animasi Berbasis PjBL (Project Based Learning) pada Materi Sistem Sirkulasi Darah Kelas XI IPA SMA/MA - Elis Yana; Khairuna Khairuna (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The application of science and technology (IPTEK) in education has generated several learning innovations, including the use of media in learning. The purpose of this research was to develop a product in the form of project-based learning (PjBL) animated videos based on the circulatory system material for grade XI in high schools, which is valid, practical, and suitable for use. Research and development (R&D) activities included data collection on student and teacher needs. The development phase aimed to produce learning media products involving media experts, subject matter experts, and biology teachers. Subsequently, the product was tested with 12 students in a limited group and then with 38 students in a broader group to determine its media feasibility. The development of PjBL-based animated video products was evaluated using instruments covering several aspects: validation sheets for media, including text composition balance, images, sound, and video, color selection, physical criteria, practicality, and long-term usefulness. Validation sheets for content included aspects of learning promotion, curiosity enhancement, presentation support, material accuracy, and student engagement. Practitioner validation sheets covered material, language, and presentation aspects, while student response questionnaires addressed material, language, and presentation. Based on the expert media validation assessment recapitulation, the overall score indicated the product was highly valid and suitable for use in learning, with an average percentage of 84.00%. Similarly, the expert content validation recapitulation showed the product to be highly valid and suitable for use in learning, with an average percentage of 88.00%. The practitioner assessment by biology teachers indicated the product was highly practical and suitable for use in learning without revision, with an average percentage of 91.19%. Additionally, the limited and broad group product tests showed an average student response rate of 85.00%, indicating that the developed animated video is suitable for use in learning without revision.